Vibration Isolation of Magnetic Suspended Platform with Double Closed-loop PID Control - Mao Tang; Jin Zhou; Chaowu Jin; Yuanping Xu (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In magnetic vibration isolation field, magnetic force is used for the isolation, while the whole isolation system is always supported passively, which have non-control shortcomings. Aimed at this problem, a novel active control strategy with a double closed-loop PID algorithm was designed in this paper. The double closed-loop strategy includes an internal and external loop control, which was designed to fulfill the magnetic levitation and isolation, respectively. Firstly, the vibration isolation strategy proposed in this paper was simulated in both time and frequency domain. The simulation results showed that this method possesses good performance of vibration isolation. Then, an active levitation and vibration isolation control experiment was designed. The experimental results showed that the control algorithm has a good vibration control effect under periodic vibration and random vibration conditions.